Neuron-Derived Exosome Proteins May Contribute to Progression From Repetitive Mild Traumatic Brain Injuries to Chronic Traumatic Encephalopathy - Goetzl, Edward J.; Ledreux, Aurélie; Granholm, Ann-Charlotte; Elahi, Fanny M.; Goetzl, Laura; Hiramoto, Jade; Kapogiannis, Dimitrios (Frontiers in Neuroscience, 2019)
The recent recognition that Alzheimer disease-like pathology may be found in chronic traumatic encephalopathy even after mild acute traumatic brain injury has increased the urgency of elucidating mechanisms, identifying biomarkers predictive of high risk of development of chronic traumatic encephalopathy and establishing biomarker profiles indicative of impactful effects of treatments. Of the many proteins that are loaded into neuron-derived exosomes (NDEs) from damaged neurons after acute traumatic brain injury, the levels of prion cellular protein, coagulation factor XIII, synaptogyrin-3, IL-6 and aquaporins remain elevated for months. Prolonged heightened expression of aquaporins and IL-6 may account for the persistent CNS edema and inflammation of chronic traumatic encephalopathy. Prion cellular protein, coagulation factor XIII and synaptogyrin-3 bind and concentrate neurotoxic forms of oligomeric Aβ peptide or P-tau for delivery to neurons at or distant from the site of trauma. Our progression factor hypothesis of chronic traumatic encephalopathy asserts that physiological neuronal proteins, such as prion cellular protein, coagulation factor XIII, synaptogyrin-3, IL-6 and aquaporins, that increase in concentration in neurons and NDEs for months after acute traumatic brain injury, are etiological contributors to chronic traumatic encephalopathy by either direct actions or by mobilizing neurotoxic forms of Aβ peptides or P-tau. Such progression factors also may be useful new targets for development of drugs to prevent chronic traumatic encephalopathy.